Fungicide efflux and the MgMFS1 transporter contribute to the multidrug resistance phenotype in Zymoseptoria tritici field isolates. (2nd March 2015) - Omrane, Selim; Sghyer, Hind; Audéon, Colette; Lanen, Catherine; Duplaix, Clémentine; Walker, Anne‐Sophie; Fillinger, Sabine
Summary: Septoria leaf blotch is mainly controlled by fungicides. Z ymoseptoria tritici, which is responsible for this disease, displays strong adaptive capacity to fungicide challenge. It developed resistance to most fungicides due to target site modifications. Recently, isolated strains showed cross‐resistance to fungicides with unrelated modes of action, suggesting a resistance mechanism known as multidrug resistance (MDR). We show enhanced prochloraz efflux, sensitive to the modulators amitryptiline and chlorpromazine, for two Z . tritici strains, displaying an MDR phenotype in addition to the genotypes CYP 51 I381V Y461H or CYP 51 I381V ΔY459/ G460, respectively, hereafter named MDR6 and MDR7. Efflux was also inhibited by verapamil in the MDR7 strain. RNA sequencing lead to the identification of several transporter genes overexpressed in both MDR strains. The expression of the MgMFS 1 gene was the strongest and constitutively high in MDR field strains. Its inactivation in the MDR6 strain abolished resistance to fungicides with different modes of action supporting its involvement in MDR in Z . tritici . A 519 bp insert in the MgMFS 1 promoter was detected in half of the tested MDR field strains, but absent from sensitive field strains, suggesting that the insert is correlated with the observed MDR phenotype. Besides MgMfs1, other transporters and mutations may be involved in MDR in Z . tritici .